Ekonomi Biaya Tinggi dalam Pelayanan Birokrasi dan Diskresi Pemerintah yang Dilematis - Syukri Hidayatullah (Fakultas Hukum Universitas Mulawarman, 2010)
It is an common matter when inefficiency bureaucracy take an advantage by cost and benefit. There is so many poor service in public sector where people need it. Grease, graft and bribery were some reason behind these problems and one from another become the manifestation of corruption. This thing is purchase and sale based the order resulted in high-cost economy. It is called corruption because discrimination for the public service was exist whos pay higher will become priority. Government seems tobe let it happen and all rules to direct the public was neglected. It’s all about the public service, the government should in charge or maybe we should know something inside bureacracy. This article would like to analyze not only merely the money spending but also to get the picture out inside bribery, grease, discretion and administration.